Biosynthesis and Mass Spectrometric Imaging of Tolaasin, the Virulence Factor of Brown Blotch Mushroom Disease. Issue 18 (12th November 2013) - Scherlach, Kirstin; Lackner, Gerald; Graupner, Katharina; Pidot, Sacha; Bretschneider, Tom; Hertweck, Christian
<x xml:space="preserve">Abstract</x> Killing them softly. The molecular basis for the biosynthesis of tolaasin, the Pseudomonas tolaasii‐derived causative agent of mushroom (Agaricus bisporus) soft rot, was revealed by genome mining and analysis of the NRPS genes. Production of the toxic lipopeptides during infection was confirmed by imaging mass spectrometry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>